A Mini-Surge on theRyder Glacier, Greenland Observed via Satelite Radar Interferometry - Joughin, I.; Tulaczyk, S.; Fahnestock, M.; Kwok, R. (2004)
A dramatic short term speed up of the Ryder glacier has been detected using satellite radar interferometry. The accelerated flow represents a substantial, though short-lived, change in the ice discharge from this basin. We believe that meltwater was involved in this event, either as an active participant, as meltwater-filled lakes on the surface of the glacier drained during the period of rapid motion.